Exploring the Impact of Professional Value and Perceived Adoption Control on Continuous Professional Development Engagement via Digital Teaching Platform : A Structural Equation Modelling Approach - Krismiyati Krismiyati; Rudy Latuperissa (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to examine the impact of professional value and perceived adoption control on teachers' CPD engagement via a digital teaching platform.  This study used a quantitative approach with a survey method. It involves 313 high school teachers in Pati, Grobogan and Semarang Central Java with at least a year of experience in using the digital teaching platform. The instrument used in this study is a 5-point Likert scale item survey with 21 questions covering 11 constructs adapted from TAM. It uses Jamovi to analyze and model the data statistically. Structural Equation Modelling examines the relationship between variables proposed in the model. The result of the study shows that perceived professional value moderately impacts teachers' CPD Engagement. The constructs strongly mediate their CPD engagement through the perceived adoption control construct. The SEM analysis indicates that the proposed model is a good fit, as the fit indices show. The conceptual implication of the findings demonstrates that it extends TAM 2 in CPD context using a digital teaching platform. Practically, CPD program should align the technology tools with teachers’ professional goals and ensure it is part of the professional culture rather than leaving it as optional or voluntary practices.